"Where Should We Eat?": How Health Consciousness Moderates the Influences Driving Intentions to Purchase Healthy Food. Issue 2 (15th March 2023) - Suttikun, Chompoonut
Abstract: Unhealthy diet patterns are a global concern in both developed and developing countries thus making food consumers consider their health and food intake more. Along with increased health consciousness, other factors might encourage food shoppers to consume healthy food products at restaurants. The goal of this study is to develop a model helping justify components affecting food consumers' attitudes and behavior of purchasing healthy food products at restaurants. Structural Equation Modeling (SEM) was used to analyze data from 500 participants. The results of the study show that personal beliefs and social norms are elements influencing consumers' attitudes while restaurant image is an important factor affecting perceptions of food products. Consumers' attitudes toward healthy food products and food prices also influenced the purchasing intentions resulting in their actual behavior of buying healthy food at restaurants. The additional significance of this study rests in showing that health consciousness moderates the effects of social norms on consumers' attitudes.